(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study applies a scientometric approach to analyze global research trends in sustainable food systems and nutritional science from 2000 to 2023. The data, drawn from the Scopus database, examines publication growth, collaboration networks, and emerging research themes. Tools such as VOSviewer and CiteSpace were employed to visualize co-authorship, citation networks, and thematic developments. Key findings reveal significant growth in publications, particularly between 2020 and 2023, reflecting an increasing global focus on food security and sustainability. India emerged as a major contributor to the field, with the Indian Council of Agricultural Research and the ICAR-Indian Agricultural Research Institute leading publication output. Additionally, India has developed strong international research collaborations, especially with the United States, United Kingdom, Australia, and China. The analysis identifies food security, climate change, and sustainable agriculture as dominant themes, while keywords like controlled study and male are underrepresented, indicating potential research gaps. Leading contributors include Varshney R.K., Jat M.L., and Siddique K.H.M., with highly cited publications shaping the discourse in sustainable food systems. The study concludes that while progress is evident, there are notable gaps, particularly in areas like precision agriculture, gender studies, and underrepresented regions. Future research should focus on these gaps to ensure a more comprehensive understanding of sustainable food systems and nutritional science, supporting global efforts toward food security and sustainability.